Nepal : Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper examines Nepal's Poverty Reduction Strategy Paper Progress Report. Recurrent expenditures remained high owing to the high military and security expenditures. The expansion of rural credits through rural credit institutions, both in the government and nongovernment sectors, the technical support and social mobilization campaign by different nongovernmental agencies, and poverty reduction programs in the government have helped improve employment opportunities in agriculture, resulting in a better life of the common people.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet